Indígena tejiendo un canasto - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1946)
SPANISH: Se observó a un papá indigena de Plantanoyacu del rio tigre con sus dos pequeños hijos uno vestido y el otro desnudo, mientras el teje un cesto o canasto de fibra de tamshi.
ENGLISH: An indigenous father from Plantanoyacu of the Tigre River was observed with his two small children, one dressed and the other naked, while he weaves a basket of tamshi fiber.

SPANISH: Se observó a un papá indigena de Plantanoyacu del rio tigre con sus dos pequeños hijos uno vestido y el otro desnudo, mientras el teje un cesto o canasto de fibra de tamshi.
ENGLISH: An indigenous father from Plantanoyacu of the Tigre River was observed with his two small children, one dressed and the other naked, while he weaves a basket of tamshi fiber.
Indigenous person weaving a basket
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Men and Women Artisans|~|Production|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Hombres y Mujeres Artesanos|~|Producción|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Men and Women Artisans|~|Production